2012
DOI: 10.1089/scd.2011.0130
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Stem Cells in the Subependymal Zone of the Adult Rodent Brain is Correlated with the Number of Ependymal Cells and Not with the Volume of the Niche

Abstract: 2The mammalian subependymal zone (SEZ; often called subventricular) situated at the lateral walls of the lateral ventricles of the brain contains a pool of relatively quiescent adult neural stem cells whose neurogenic activity persists throughout life. These stem cells are positioned in close proximity both to the ependymal cells that provide the cerebrospinal fluid interface and to the blood vessel endothelial cells, but the relative contribution of these 2 cell types to stem cell regulation remains undetermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Factors secreted by the ependyma may be particularly critical in the SVZ niche, as recent evidence suggests that NSC scale proportionally to the number, rather than volume of ependymal cells (Kazanis and Ffrench-Constant, 2012). Unlike other growth factor treatments that typically target one step in the differentiation cascade of the B cell, and often deplete the NSC niche (including Shh, Egf, Wnt, and Lif), by promoting terminal differentiation (Encinas et al, 2011), or disorganization of the niche (Kokovay et al, 2012), noggin promoted the proliferation of adult SVZ progenitors at multiple stages of their differentiation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Factors secreted by the ependyma may be particularly critical in the SVZ niche, as recent evidence suggests that NSC scale proportionally to the number, rather than volume of ependymal cells (Kazanis and Ffrench-Constant, 2012). Unlike other growth factor treatments that typically target one step in the differentiation cascade of the B cell, and often deplete the NSC niche (including Shh, Egf, Wnt, and Lif), by promoting terminal differentiation (Encinas et al, 2011), or disorganization of the niche (Kokovay et al, 2012), noggin promoted the proliferation of adult SVZ progenitors at multiple stages of their differentiation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with reports revealing enhanced efficiency in culturing neural progenitors under hypoxia (Stacpoole et al, 2013 ). On the other hand, we have shown that in evolution—for example, when comparing rodent brains of different sizes—the number of adult NSCs that populate the niche correlates strictly with the number of ependymal cells and not with the volume of the niche that would reflect the volume of the vasculature (Kazanis and ffrench-Constant, 2012 ). This strengthens the hypothesis that during evolution/development the role of the vasculature becomes crucial for NSCs after they have been established in the system.…”
Section: The Role Of the Vasculaturementioning
confidence: 99%
“…Adult NSCs remain in a stage of quiescence (Doetsch et al, 1999 ). We have shown that NSCs are preferentially positioned next to the ependyma (Kazanis et al, 2010 ; Kazanis and ffrench-Constant, 2012 ), which produces pro-neurogenic signals such as noggin (Lim et al, 2000 ). However, recent experimental work revealed that NSC quiescence is controlled via direct cell-to-cell contacts with endothelial cells (Ottone et al, 2014 ) and via the activity of diffusible endothelium-derived factors such as neurotrophin-3, angiopoietins 1 and 2 and placental growth factor 2 (PlGF-2; Masjkur et al, 2012 ; Delgado et al, 2014 ; Crouch et al, 2015 ; see also reviews of Goldman and Chen, 2011 ; Ottone and Parrinello, 2015 ).…”
Section: The Role Of the Vasculaturementioning
confidence: 99%
“…For example, ependymal cells are a critical component of the SVZ stem cell niche, and their cell number within the neurogenic zone correlates with stem cells number and neurogenesis (5456). Among the identified mechanisms by which ependymal cells regulate stem cell function is the negative regulation of BMP signaling through expression of LRP2 (55).…”
Section: Components Of the Brain Tumor Stem Cell Nichementioning
confidence: 99%